Faunistic study of Coleoptera (Buprestidae, Carabidae, Cerambycidae, Lucanidae and Melyridae) on Gageodo Island, south-westernmost Korean Peninsula - Donguk Kim; Dooyoung Kim; Dongmin Kim; Young-Kun Kim; Sang Jae Suh; Kwang Shik Choi (Biodiversity Data Journal)
The Korean Archipelago consists of more than 3,348 islands, many of which have an intact biodiversity. Gageodo Island, which is the south-westernmost island in the Peninsula, is characterised by floristic and faunistic features that are distinct from those of the mainland, making it of biogeographical and ecological interest. However, due to the difficulties associated with surveying this Island, it remains under-investigated. In particular, the Island's coleopteran fauna remains poorly understood.In this study, the authors surveyed Buprestidae (jewel beetles), Carabidae (ground beetles), Cerambycidae (longhorn beetles), Lucanidae (stag beetles) and Melyridae (soft-winged flower beetles) on Gageodo Island. Each species was identified and ecological notes were recorded. To update the coleopteran list for the Island, previous studies that examined samples from Gageodo Island were compiled and organised. As a result, 31 species and three families were recorded on the Island for the first time, for a total of 93 species within 16 families. Of these, the melyrid species, Intybia tsushimensis (Satô & Ohbayashi, 1968) is reported for the first time in the Korean Peninsula. This study contributes to understand the coleopteran fauna of the biogeographically important Island in Korea and will serve as a foundational piece for understanding the fauna of Gageodo.